Natural Resource Management and Institutional Dynamics: Myanmar and Indonesia in Comparative Perspective - Fitristanti, Salsabila; Muhyidin, Ali (UI Scholars Hub, 2021)
Natural resource management in the conflict area has raised a debate on how institutions adapt to conflict conditions. This paper utilizes Institutional Analysis and Development (IAD) framework provided by Ratner by conducting a multi-case comparative specifying on the sub-national in Kachin (Myanmar) and Papua (Indonesia). The analysis focuses on how the institutional dynamics relate to collective action in the mining operation during the ongoing conflict. The empirical investigation shows that the different results occurred due to the diverse decentralization arrangement. The case in Kachin indicates some degree of difficulties in the decentralization arrangement. This condition raises the lack of transparency and participation, which implicates the unequal developments for local people. On the other hand, Papua’s case demonstrates the progress of systemic transformation and changing legal framework. The output reflected some improvements, though there is some degree of on its implementation.